2019
DOI: 10.1002/jcb.29556
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 attenuates cardiomyocyte apoptosis and inflammation via the TLR4/NF‐kB/NLRP3 pathway

Abstract: Sepsis‐induced myocardial dysfunction (SIMD) causes high mortality in seriously ill patients. Ginsenoside Rg1 has been proven to have effective anti‐inflammatory and antiapoptotic properties. However, the specific role of Rg1 in SIMD and the molecular mechanism remain unclear. Hence, we aimed to investigate the latent effects of ginsenoside Rg1 against SIMD and explore its underlying mechanisms. Male C57BL/6J mice and neonatal rat cardiomyocytes (NRCMs) were used as in vivo and in vitro models, respectively. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(87 citation statements)
references
References 39 publications
1
76
0
Order By: Relevance
“…Tlr4 can activate myeloid differentiation factor 88 (Myd88)-dependent pathways (6). Tlr4 can also regulate the transcriptional activity of nF-κB and interferon regulating factor 3 (IRF3), which promotes the production of inflammatory factors (7)(8)(9). as a member of Tlr family, Tlr2 can participate in the inflammatory response by modulating the Myd88 signaling pathway, and the activation of nF-κB and mitogen activated protein kinase (MaPK) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Tlr4 can activate myeloid differentiation factor 88 (Myd88)-dependent pathways (6). Tlr4 can also regulate the transcriptional activity of nF-κB and interferon regulating factor 3 (IRF3), which promotes the production of inflammatory factors (7)(8)(9). as a member of Tlr family, Tlr2 can participate in the inflammatory response by modulating the Myd88 signaling pathway, and the activation of nF-κB and mitogen activated protein kinase (MaPK) (10).…”
Section: Introductionmentioning
confidence: 99%
“…The present study found that IL-32 also promoted TLR4, NOD1 and NOD2 expression in a concentration-dependent manner. Notably, NOD1/2 and TLR4 are known to activate NF-κB signaling, which is able to trigger NLRP3 activation (36)(37). Therefore, the present results indicated that IL-32 could also induce inflammation and NLRP3-mediated pyroptosis by activating pattern recognition receptors.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that the inhibition of NLRP3 inflammasome activity could significantly decrease tissue inflammatory damage and inhibit apoptosis in LPS-induced acute kidney injury (53). A recent study reported that Rg1 could attenuate LPS-induced inflammation and apoptosis both in neonatal rat cardiomyocytes and septic mice and restore impaired cardiac function by blocking the TLR4/NF-κB/NLRP3 pathway (54). It has been reported that excessive ROS generation can activate the NLRP1 inflammasome and induce macrophage apoptosis in vitro and in vivo; although these effects can be significantly inhibited by pretreatment with ROS inhibitors (55).…”
Section: Discussionmentioning
confidence: 99%